The Importance of Work Preparation for Residents of Babakan Banten Hamlet: Building Personal Branding and Writing CV - Hikmawati, Amelia Sofiana; Annisa, Syifa; Nasution, Rahmat Hamdani; Pangestuti, Rinda Siaga; Khatimah, Husnul (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This study underscores the importance of work preparation before entering the workforce, focusing on personal branding and skills crucial for professional success. Addressing Babakan Banten Hamlet residents' need for work readiness awareness, it guides youth in crafting effective CVs and job application letters. Utilizing mixed methods, qualitative interviews, and quantitative surveys assess community needs and program efficacy perceptions. Method: Community engagement involves workshops for 17 to 22-year-olds. Data collected through observation and surveys assesses training effectiveness. Practical Applications: This research empowers participants for better job market entry, improved job application outcomes, and potentially higher youth employment rates, contributing to community growth. It also informs similar community development approaches. Conclusion: This activity strives to prepare Babakan Banten Hamlet's youth for the workforce through essential skills training. Its potential impact on employability and community well-being underscores the importance of targeted engagement in addressing specific challenges.